Morphometric MRI assessment of lumbar region in healthy individuals (Annals of Medical Research, 2021)
Aim: In our study, we aimed to obtain normal anatomical data in healthy individuals by magnetic resonance imaging, which we frequently use in our daily practice. We encounter quite frequently with the lumbar pathologies. To identify the pathological one, the normal one must first be defined. For this, anatomical studies are the most ideal methods, but costly and challenging studies. Morphometric assessment of the lumbar region by magnetic resonance imaging in the normal population is not common in the literature.Material and Methods: The workup of 100 patients who presented to our clinic, did not have low back pain, underwent lumbar MRI examination for different reasons and whose results were reported to be normal, were evaluated using the PACS system. Morphological evaluation of the paravertebral muscles, ligamentum flavum, and the spinal canal was performed on the right and left sides separately. The data were analyzed by age, gender, and body mass index.Results: Forty-nine patients were females, and 51 were males. The mean age of the patient group was 34.62±9.54 years, and mean BMI was 24.96±3.32 kg/m2. Ligamentum flavum thickness and muscle areal measurements were similar between both sides. The comparisons of clinical measurements between females and males revealed that the areas of muscles were significantly higher among males and all other measurements were similar between sexes. There was a weak and positive correlation between age and both right and left erector spinae area. The only parameters that weakly and positively correlated with body mass index were right and left erector spinae areas.Conclusion: In our study, we reported the morphological characteristics of the lumbar region in healthy individuals. An increase in the cross-sectional areas of the erector spinae and the spinal canal at the L5-S1 level was observed with the age. An asymmetry may develop in LF measurements with the age. There was also a positive correlation between body mass index and the cross-sectional area of erector spinae.